Ethical organisational culture, effective internal control systems and tax compliance of small and medium scale enterprises (SMEs): The role of corporate governance - Alhassan Musah; Abigail Padi; Marshall Wellington Blay; Daniel Odei Okyere; Benjamin Siaw Ofori (Social Sciences and Humanities Open)
Literature on tax compliance of SMEs have focused on economic factors, behavioural factors and psychological factors ignoring important factors like ethical organisational culture (EOC) and effective internal control system (EICS) on tax compliance. The study also included corporate governance (CG) as a moderator within the unique context of agency theory. The purpose of the study is to examine the effect of ethical organizational culture and effective internal control systems on tax compliance for a sample size of 566 SMEs in Ghana, using corporate governance as a moderating variable. The study collected data using structured questionnaire and analysed same using PLS-SEM. The results of the hypothesis testing showed that ethical organisational culture, effective internal control systems and corporate governance have a significant positive effect on SMEs tax compliance with EIC having the most significant influence on tax compliance behaviour among SMEs. The combined effect of corporate governance and ethical organizational culture strengthens their interactive role in reinforcing tax compliance. Additionally, the interaction between corporate governance and effective internal control system is positive and significant with SMEs' tax compliance in Ghana. The novelty of this study is the inclusion of variables such as ethical organisational culture and effective internal control system as factors influencing tax compliance behaviour of SMEs which have not received much attention in literature.